Experiences of support from primary care and perceived needs of parents bereaved by suicide: a qualitative study - Wainwright, Verity (Br J Gen Pract, 2020)
BACKGROUND: People bereaved by suicide are a vulnerable group, also at risk of dying by suicide. The importance of postvention support (intervention after suicide) has recently been highlighted; however, little is known about the support needs of parents bereaved by suicide in the UK, and the role played by general practice. AIM: To explore the perspectives, experiences, and support needs of parents bereaved by suicide. DESIGN AND SETTING: This was a qualitative study, with semi-structured interviews conducted between 2012 and 2014 in the north of England and the Midlands, with parents bereaved by their son or daughter’s suicide. METHOD: Interviews explored parents’ experiences of suicide bereavement following the death of their son or daughter, with a focus on their experiences of support from primary care. Interviews were analysed thematically using constant comparison. RESULTS: Twenty-three interviews were conducted. Three themes were identified from the data: the importance of not feeling alone; perceived barriers to accessing support; and the need for signposting for additional support. Some parents reported having experienced good support from their general practice; others described a number of barriers to accessing help, including triage processes. Primary care was considered to be an important avenue of support but GPs were often perceived as uncertain how to respond. The need for information, signposting to avenues of support, and the helpfulness of group support were also highlighted. CONCLUSION: Parents believed it was important that people working in general practice have an awareness of suicide bereavement and understanding of their needs, including knowledge of where to direct people for further support.